Does community size or commute time affect severity of illness at diagnosis or quality of care in a centralized care model of pulmonary hypertension?. (1st June 2021) - Brunner, Nathan W.; Legkaia, Lena; Al-Ahmadi, Fayez; Lee, Lisa; Norena, Monica; Lam, Charmaine S.M.; Yim, Jeffrey J.; Luong, Christina; Weatherald, Jason; Nador, Roland G.; Levy, Robert D.; Swiston, John R.
Abstract: Background: Centralized care models are often used for rare diseases like pulmonary hypertension (PH). It is unknown how living in a rural or remote area influences outcomes. Methods: We identified all patients from our PH database who carried a diagnosis of WHO Group 1 or WHO Group 4 PH. Using Canadian postal code data, patients were classified as living in a rural area; or a small, medium or large community size. The commute time from patient residence to our clinic was determined using mapping software. We compared baseline catheterization data according to community size and commute time. At follow up, we evaluated the association between community size and commute time with prognostic parameters of functional class, walk distance and echocardiography. Results: Of the 342 patients identified, 72(21%) patients lived in rural areas, while 26(8%), 49(14%) and 195(57%) resided in small, medium and large population centres, respectively. The commute time was <1 h for 160(47%), 1–3 h for 62(18%), and >3 h for 120(35%). There was no association seen for any catheterization parameter by either community size or commute time. At last follow up, there was no association between any prognostic parameter and community size or commute time. Conclusions: We found no association between community size or commute time with severity of illness at diagnosis, or markers of prognosis at follow up. This suggests that patients who reside in rural or remote environments are not experiencing deficiencies in care compared to urban patients. Highlights: In pulmonary hypertension, care is centralized in "Centers of Excellence". It is unclear how this effects patients who live in remote or rural places. We found no association with severity of illness at diagnosis on catheterization. We found no change in type of care, follow up tests or low risk status. Patients who live in rural or remote areas do well with centralized care.